The Axiology of Da'wah Science: Islamic Community Development (PMI) in Supporting Social Workers - Ramadhan, Dimas Afditiya; Syukur, Abdul (EDUCATIO : Journal of Education, 2023)
This research explores the axiological aspects of Islamic Da'wah and its role in supporting social workers in the context of Islamic Community Development (PMI). Utilizing qualitative methods and interviews, the study uncovers how Islamic Da'wah's values and ethics form a robust moral foundation for PMI's social work. Core values like justice, compassion, wisdom, and integrity guide PMI's approach, addressing social inequalities, fostering a caring community through empathy, making wise decisions, and upholding ethical standards. This axiological framework empowers PMI to engage in high-integrity social work, positively impacting the Muslim community and fostering sustainable change. Additionally, social work principles such as acceptance, communication, individualization, participation, confidentiality, and self-awareness underpin their practices. Integrating religion and spirituality into social work is essential, with Islam emphasizing collective and individual responsibilities for communal welfare. Muslim social workers apply Islamic concepts like prayer, almsgiving, fasting, and pilgrimage in their work, creating an effective and ethical framework. Within the Muslim context, integrating fundamental Islamic concepts into social work is vital. The principle of tawhid emphasizes respecting all humans as creations of Allah, regardless of background. Zakat highlights the need to assist the poor equitably, fasting promotes empathy, and the pilgrimage underscores global solidarity. By applying these principles, Muslim social workers offer holistic services grounded in Islamic values, enhancing individuals' and communities' quality of life within the broader Muslim society.